Influence of Standard Tannin and Standard Saponin on Methane Mitigation and Rumen Fermentation Characteristics for Ruminants - A, Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Methane is one of the important green house gas, which is normally emitted from ruminants and represents a loss of feed energy by 8-12 per cent. A huge number of feeding strategies are used to mitigate the methane emission from ruminants for sustainable animal production. Hence an experiment was conducted to study the influence of standard tannin (ST) and standard saponin (SS) on methane mitigation and rumen fermentation characteristics for ruminants by in vitro gas production technique (IVGPT). The IVGPT was carried out by incubating the Cumbu Nappier hybrid (CN-CO4) grass and rumen liquor with ST + SS at varying levels viz., 0, 1.03 per cent + 0.78 per cent, 2.06 per cent + 1.56 per cent, 3.09 per cent + 2.34 per cent and 4.12 per cent + 3.12 per cent of substrate in six replicates for a period of 24 hours in shaking water bath. After 24 hours the total gas production and pH were measured and methane was estimated in Gas Chromatography. The in vitro true dry matter digestibility (IVTDMD) was estimated and methane emission (ml) per 100 mg truly digested substrate was calculated. The rumen fermentation characteristics were also studied. The total gas production was significantly (p<0.0) decreased in all ST + SS added groups and the maximum reduction was observed in 3.09 per cent ST + 2.34 per cent SS added group than control. The methane emission was significantly (p<0.01) decreased by 26.03, 29.75, 38.02 and 40.91 per cent in 1.03 per cent + 0.78 per cent, 2.06 per cent + 1.56 per cent, 3.09 per cent + 2.34 per cent and 4.12 per cent + 3.12 per cent ST + SS supplemented groups respectively than control. The minimum level of ST + SS that reduced the methane emission per 100 mg truly digested substrate (35.64 per cent) was 3.09 per cent + 2.34 per cent when compared to control. The rumen fermentation characteristics viz. ammonia nitrogen, IVTDMD, bacterial and protozoal population was significantly decreased in ST + SS added groups than control. The pH of the fermented medium was not altered in all the treatment groups. The TVFA, propionic acid and butyric acid were significantly increased in standard tannin and saponin added groups than control. The acetic acid and acetate to propionate (A/P) ratio were significantly reduced in ST + SS treated groups when compared to control. It was concluded that at minimum concentration of 3.09 per cent ST + 2.34 per cent SS significantly reduced the methane emission and methane (ml) per 100 mg of truly digested substrate (p<0.01) than control without any adverse effect on rumen fermentation characteristics by IVGPT.